Critical scale grain size for optimal lifetime of TBCs. (10th July 2022) - Chen, Lin; Meng, Guo-Hui; Li, Chang-Jiu; Yang, Guan-Jun
Highlights: The critical scale grain size d c of ∼2.5 μm is identified for optimal TBC lifetime. When d < d c, the rapid growth of the scale causes delamination failure of TBCs. When d > d c, the growth stress causes vertical cracking and early failure of TBCs. Abstract: Thermal barrier coatings (TBCs) suffer from spalling failure resulting from the rapid growth of thermally grown oxides (TGO) on the metallic bond coat. In this study, to achieve the optimal lifetime of TBCs, a lifetime phase diagram was constructed for the entire service of TBCs. Herein, both the thermal mismatch stress during thermal cycling and the TGO growth stress during thermal exposure were considered. First, thickening behavior of the Al2 O3 scale related to grain size was investigated. Second, transverse delamination failure due to the thermal mismatch stress was analyzed. Third, vertical cracking failure related to early scale growth was explored. Finally, a critical scale grain size of ∼2.5 μm was identified for achieving the optimal lifetime of TBCs. It was experimentally proved that vertical cracking of the Al2 O3 scale occurred during early oxidation as the scale grain size was larger than ∼4 μm after pre-oxidation. The proposed lifetime phase diagram and critical scale grain size effect serve as novel criteria for the design of next-generation durable TBCs. Graphical abstract: Image, graphical abstract